2012
DOI: 10.1007/bf03256436
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Levels and Vitamin D Receptor Polymorphisms as Markers in Predicting Cachectic Syndrome in Cancer Patients

Abstract: Background and Objective: In patients with advanced cancer, cachexia correlates with low performance status and poor quality of life. In addition, cachexia may be associated with reduced response to chemoradiotherapy and a poor prognosis in cancer patients. Nearly all forms of cachexia are closely associated with chronic inflammation and elevated levels of inflammatory and pro-inflammatory circulating factors, including C-reactive protein (CRP), which is considered a valid laboratory and clinical marker. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…C1 patients had the highest systemic inflammation, lowest nutritional status and dramatically poorest prognosis (Table 2). As previously described by our research group (Punzi et al, 2012), CRP proved to be one of the most reliable and economic blood markers for CACS that a standard clinical laboratory can study (Mahmoud and Rivera, 2002). A standard nutritional status assessment usually includes the determination of albumin serum level, despite the open discussion regarding which albumin threshold should be chosen for the diagnosis of malnutrition.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…C1 patients had the highest systemic inflammation, lowest nutritional status and dramatically poorest prognosis (Table 2). As previously described by our research group (Punzi et al, 2012), CRP proved to be one of the most reliable and economic blood markers for CACS that a standard clinical laboratory can study (Mahmoud and Rivera, 2002). A standard nutritional status assessment usually includes the determination of albumin serum level, despite the open discussion regarding which albumin threshold should be chosen for the diagnosis of malnutrition.…”
Section: Resultsmentioning
confidence: 93%
“…We recently demonstrated that cancer patients with CACS have higher C-Reactive Protein (CRP) levels compared with non-cachectic cancer patients (Punzi et al, 2012), thus reinforcing the hypothesis that the chronic inflammatory state commonly observed in advanced cancers is linked to the aetiology of CACS (MacDonald, 2011). Aberrant immune system activity is a crucial aspect of the chronic systemic inflammation associated with CACS and it triggers a vicious cycle leading to further tumour growth and metastases.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…To date most of the studies on identification of SNPs involved in cancer cachexia has led to the discovery of other SNPs involved in the innate immune system, mainly in the interleukin family of cytokines (Jatoi et al 2007(Jatoi et al , 2010Knoll et al 2008;Zhang et al 2008;Deans et al 2009;Bo et al 2010;Rausch et al 2010;Sun et al 2010a, b) (table 1). SNPs in other biological processes have also been studied for their association with cancer cachexia (Solheim 2011(Solheim , 2012Punzi et al 2012) (table 1). By altering the phenotype for a degree of skeletal muscle quantification, it may be possible to identify SNPs associated with muscle tissue biology.…”
Section: Introductionmentioning
confidence: 99%